Failing to Become a Subject: An Existential Feminist Reading of the Character of Si Cantik Malam in Eka Kurniawan’s Short Story - Mahfudz, Abdullah Zufar; Purnomo, Faradillah Bilqis Kartika Tsani; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the representation of female existence in the short story Si Cantik yang Tak Boleh Keluar Malam by Eka Kurniawan using the framework of existential feminism proposed by Simone de Beauvoir. The research focuses on analyzing the forms of restriction imposed on women within a patriarchal family structure, the protagonist’s acts of resistance, and the meaning of failure in achieving liberation from an existential feminist perspective. A qualitative descriptive method is employed with content analysis as the main technique. The data consist of textual excerpts that illustrate power relations, bodily control over the female character, and her responses to the restricting social system. The findings reveal that the character Si Cantik experiences existential limitations enforced by familial authority, represented by the father as a patriarchal figure. Her attempts at resistance do not lead to liberation but instead result in failure and social marginalization. This failure demonstrates that patriarchy operates not only within the domestic sphere but is also reinforced by society through stigma and narrative construction. The study concludes that the short story reflects the complexity of women’s struggle to achieve subjectivity and autonomy within a deeply patriarchal social system.